Indirect Export of Reducing Equivalents From the Chloroplast to Resupply NADP for C3 Photosynthesis—Growing Importance for Stromal NAD(H)? - Krämer, Moritz; Kunz, Hans-Henning (Frontiers in Plant Science, 2021)
Plant productivity greatly relies on a flawless concerted function of the two photosystems (PS) in the chloroplast thylakoid membrane. While damage to PSII can be rapidly resolved, PSI repair is complex and time-consuming. A major threat to PSI integrity is acceptor side limitation e.g., through a lack of stromal NADP ready to accept electrons from PSI. This situation can occur when oscillations in growth light and temperature result in a drop of CO2 fixation and concomitant NADPH consumption. Plants have evolved a plethora of pathways at the thylakoid membrane but also in the chloroplast stroma to avoid acceptor side limitation. For instance, reduced ferredoxin can be recycled in cyclic electron flow or reducing equivalents can be indirectly exported from the organelle via the malate valve, a coordinated effort of stromal malate dehydrogenases and envelope membrane transporters. For a long time, the NADP(H) was assumed to be the only nicotinamide adenine dinucleotide coenzyme to participate in diurnal chloroplast metabolism and the export of reductants via this route. However, over the last years several independent studies have indicated an underappreciated role for NAD(H) in illuminated leaf plastids. In part, it explains the existence of the light-independent NAD-specific malate dehydrogenase in the stroma. We review the history of the malate valve and discuss the potential role of stromal NAD(H) for the plant survival under adverse growth conditions as well as the option to utilize the stromal NAD(H) pool to mitigate PSI damage.